Structural lubricity of physisorbed gold clusters on graphite and its breakdown: Role of boundary conditions and contact lines - Gao, Hongyu; Müser, Martin H. (Frontiers in Chemistry, 2022)
The sliding motion of gold slabs adsorbed on a graphite substrate is simulated using molecular-dynamics. The central quantity of interest is the mean lateral force, i.e., the kinetic friction rather than the maximum lateral forces, which correlate with the static friction. For most set-ups, we find Stokesian damping to resist sliding. However, velocity-insensitive (Coulomb) friction is observed for finite-width slabs sliding parallel to the armchair direction if the bottom most layer of the three graphite layers is kept at zero stress rather than at zero displacement. Although the resulting kinetic friction remain much below the noise produced by the erratic fluctuations of (conservative) forces typical for structurally lubric contacts, the nature of the instabilities leading to Coulomb friction could be characterized as quasi-discontinuous dynamics of the Moiré patterns formed by the normal displacements near a propagating contact line. It appears that the interaction of the graphite with the second gold layer is responsible for the symmetry breaking occurring in the interface when a contact line moves parallel to the armchair rather than to the zigzag direction.